5 - Internet et enjeux de pouvoir dans le champ universitaire ivoirien - Aghi Bahi,; Gadou Dakouri, (Africa Media Review, 2008)
In the context of Ivorian universities characterised by an acute lack of documentary resources and a shortage of relevant infrastructure, one could easily believe, like the advocates of technology and of the knowledge society, that the Internet, with its numerous uses (documentation, publication, etc.), would serve as a readymade palliative to this deficiency. At the same time, the Internet would be thought of as an alternative for upward mobility and even for domination in the university space. However, empirical evidence points to the fact that the Internet remains a tool in the hands of a happy few only. How can this contrasted attitude towards Internet among its university users be accounted for? This paper seeks to examine the views of the various protagonists, while focusing on issues relating to domination within the university arena. These views were obtained through a qualitative survey of a good number of lecturers from the University of Cocody. It stands out that though personal ambition and power play constitute structuring elements of the university space, they heavily constrain the establishment of a veritable platform for intellectual activities. Thus, the consolidation of a knowledge society goes beyond mere issues of technology